0325 High-Throughput Sleep Phenotyping and Heritability in Diversity Outbred Mice. (27th April 2018) - Keenan, B T; Galante, R; Lian, J; Simecek, P; Gatti, D M; Zhang, L; Lim, D C; Svenson, K L; Churchill, G; Pack, A I
Abstract: Introduction: High-throughput phenotyping is essential for genetic association studies in outbred mouse populations such as the Diversity Outbred (DO). This study describes a strategy utilizing activity-based measures of sleep and circadian traits, including phenotype assessment, reproducibility and heritability, in DO mice and their 8 inbred and wild-derived founders. Methods: Phenotypes were measured within age-matched male DO mice (n=338) and the 5 common [A/J (n=6), C57BL/6J (n=14), 129S1/SvlmJ (n=6), NOD/LtJ (n=6), NZO/H1LtJ (n=6)] and 3 wild-derived [CAST/EIJ (n=8), PWK/PHJ (n=8), WSB/EIJ (n=6)] inbred founders. A sleep definition of ≥40 seconds of continuous inactivity using infrared beams was utilized to quantify sleep/wake amounts and bout characteristics in light and dark phases. Latency to sleep (vigilance), multiple sleep latency test (MSLT), response to sleep deprivation, and circadian period (using wheel running) were also estimated. Reproducibility was calculated using Intraclass Correlation Coefficients (ICCs) from repeated assessments. Narrow-sense heritability (h 2 ) was calculated as the proportion of variability explained by additive genetic effects using genotype data in DO mice, and broad-sense heritability (H 2 ) calculated as the proportion of variability explained by genotype in founders. Results: Most phenotypes were reproducible within individual mice, with ICC≥0.60. Sleep and wake phenotypes using alternative definitions of ≥20, ≥60 or ≥80 seconds of inactivity were highly correlated (ρ>0.85) with primary measures (≥40 seconds), demonstrating the robustness of the sleep definition. Differences in all traits were seen between founder strains and there was moderate-high heritability for most phenotypes; sleep/wake characteristics during lights-off and circadian period were the most heritable (H 2 =54–60%). There was large phenotypic variability among DO mice; values covered and extended beyond the range across founders. Estimates of heritability were lower in DO mice than in founders, with circadian period the most heritable (h 2 =36%). This may reflect unmeasured non-additive genetic effects. Conclusion: A high-throughput phenotyping strategy based on monitoring of activity patterns in mice provides reproducible estimates of sleep and circadian characteristics with evidence of heritability. This paradigm is suitable for use in DO mice, where genetic factors explain some proportion of phenotypic variability. Support (If Any): NIH grant R01 HL111725.